The herpetological legacy of Jacob Green and the nomenclature of some North American lizards and salamanders - Pyron, R. Alexander; Beamer, David A. (Zootaxa, 2020)
Jacob Green was born in 1790 to a prominent New Jersey family of scholars and theologians. He taught at the College of New Jersey (now Princeton University) from 1818 to 1822 before co-founding Jefferson Medical College (now Thomas Jefferson University) in 1825, where he taught Chemistry until his death in 1841. Between 1818 and 1831, he published a series of nine papers on lizards, salamanders, and snakes, authoring the original description of several well-known species of salamanders from the eastern United States. Many of his names are ambiguous; some have been adjudicated by the ICZN, while others are currently treated as nomina dubia. Here, we review all of Green’s publications, report on newly re-discovered or re-interpreted material from several major natural history collections, and resolve most if not all remaining issues through a series of taxonomic actions. In particular, we first designate a neotype for Salamandra nigra Green, 1818. We then place S. sinciput-albida Green, 1818 and S. frontalis Gray in Cuvier, 1831 in synonymy with S. scutata Temminck in Temminck & Schlegel, 1838 and invoke Reversal of Precedence under Article 23.9 to designate them nomina oblita. We also designate a lectotype for S. bislineata Green, 1818. Finally, we resurrect the name S. fusca Green, 1818 as the valid name for the species Desmognathus fuscus, assuming priority over Triturus fuscus Rafinesque, 1820, designating S. fusca Laurenti, 1768 a nomen oblitum, and placing S. nigra Green, 1818 in synonymy. While Green’s herpetological legacy is not as expansive as that of some of his successors such as Holbrook, he is nonetheless a foundational early worker in salamanders, having described some of the most-studied species in the world.